Fresh-keeping functional water-based master batch suitable for corrugated case as well as preparation method and application of fresh-keeping functional water-based master batch
By using nanocomposite antibacterial agents and organic gas adsorbent materials in corrugated cartons, the problem of poor performance in fruit and vegetable preservation is solved, and the efficient preservation effect is achieved without adding processes, meeting food-grade standards, and extending the preservation time of fruit and vegetable.
Patent Information
- Application Number
- CN202411781461.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
AI Technical Summary
The existing corrugated cartons are not effective in preserving fruits and vegetables, and there is a lack of fresh-preserving slurry on the market that meets food-grade standards.
A fresh-keeping function aqueous masterbatch suitable for corrugated cartons is developed. Nano-scale aqueous masterbatch with antibacterial, anti-mold and gas adsorption functions are prepared by combining nanocomposite antibacterial agents, organic gas adsorption materials and aqueous resins, and the masterbatch is added during the slurry process of corrugated cartons.
It can improve the preservation effect of fruits and vegetables without adding processes during the production process of corrugated cartons, meet the national standards for food contact materials, and extend the preservation time of fruits and vegetables through antibacterial and gas adsorption.
Smart Images

Figure BDA0005172882090000021 
Figure BDA0005172882090000061 
Figure BDA0005172882090000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of food preservation, in particular to a water-based masterbatch with a fresh-keeping function suitable for corrugated paper boxes, and a preparation method and application thereof. Background Art
[0002] Whether it is normal fruit and vegetable bulk trade or small-scale fruit and vegetable sales, corrugated boxes are the most commonly used packaging for fruits and vegetables. Especially in the current e-commerce era, online shopping has long become a part of people's daily life. In the past, the way to buy fruits and vegetables was simply to go to fruit and vegetable stores and wholesale markets offline, but now online shopping for fruits and vegetables is more convenient and faster, especially for some seasonal fruits and local specialty fruits. And corrugated boxes have become one of the most commonly used ways to transport most fruits and vegetables because of their good quality and low price.
[0003] The corrugated paper boxes on the market are only a layer of packaging for fruits and vegetables, which provides simple protection and has little effect on the preservation of fruits and vegetables. The production process of corrugated paper boxes, such as pulping, papermaking, box design and production, and cost reduction, has long been very mature.
[0004] From the perspective of fresh-keeping technology, in the entire process, when making food-grade corrugated paper pulp, materials with fresh-keeping ingredients are made into mixed pulp, and after the corrugated paper with fresh-keeping effect is made, it is made into corrugated paper boxes through normal processes. This is a relatively simple and cost-saving method. For fresh-keeping materials for fruits and vegetables, in addition to meeting the basic fresh-keeping function requirements, they must also comply with the national standards for food contact materials. At present, most of the pulps on the market are only industrial grade and fail to meet the food grade requirements, and there are very few pulps used for fruit and vegetable preservation. Therefore, it is necessary to design a fresh-keeping function water-based masterbatch suitable for corrugated paper boxes and its preparation method and application. Summary of the invention
[0005] In order to overcome the defects in the prior art, a water-based masterbatch with a fresh-keeping function suitable for corrugated paper boxes and a preparation method and application thereof are provided.
[0006] The present invention is achieved through the following solutions:
[0007] A water-based masterbatch with a fresh-keeping function suitable for corrugated paper boxes, wherein the fresh-keeping function water-based masterbatch comprises the following components in parts by mass:
[0008]
[0009] The water-based resin is at least one or more of polyacrylate emulsion, polyurethane emulsion, and acrylic acid-acrylate copolymer emulsion.
[0010] The nano composite antibacterial agent is at least one or more of nano titanium dioxide, magnesium silicate, sorbic acid, borax, methyl parahydroxybenzoate, propyl parahydroxybenzoate, sodium boric oxide and sodium thiosulfate.
[0011] The organic gas adsorption material is at least one or more of silicon dioxide, silica gel, molecular sieve, diatomaceous earth and kaolin.
[0012] The viscosity modifier is at least one or more of bentonite, ethyl cellulose and hydroxyethyl cellulose.
[0013] The lubricant is at least one or more of alkyl-modified silicone oil, butyl octadecanoate, and polydimethylsiloxane.
[0014] The dispersant is at least one or more of an aluminate dispersant, a polyethylene glycol dispersant, and polyethylene oxide;
[0015] The surfactant is at least one or more of sodium succinate sulfonate, sorbitan tristearate, and polyoxyethylene sorbitan monooleate;
[0016] The defoaming agent is at least one or more of an organosilicon defoaming agent and an organic-acetylene defoaming agent.
[0017] The average particle size of the fresh-keeping functional water-based masterbatch is 0.1-500nm.
[0018] A method for preparing a water-based masterbatch with a fresh-keeping function suitable for corrugated paper boxes, the method comprising the following steps:
[0019] S1. The nano-composite antibacterial agent and ultrapure water were added to a food-grade coating-type horizontal zirconia three-roll mill, the roller pitch was adjusted to 3-5 microns, and the speed was 500-1500r / min for grinding for 0.5-5h. After grinding, the microfiltration was performed through a microporous membrane, and the filtrate was a micron-grade nano-composite antibacterial agent solution;
[0020] S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is ground by a nano-sized zirconium oxide sand mill at a speed of 100-3800 r / min for 1-6 h, and the grinding is stopped after the particle size reaches the standard of 0.1-500 nm by particle size detection, and the filtrate is filtered and separated by an ultrafiltration membrane to obtain a nanocomposite antibacterial agent solution;
[0021] S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent;
[0022] S4. The organic gas adsorbent material and ultrapure water were added to a food-grade coating-type horizontal zirconia three-roll mill, the roller pitch was adjusted to 3-5 microns, and the speed was 500-1500r / min for grinding for 0.5-5h. After grinding, the microporous membrane was microfiltered to obtain a micron-sized organic gas adsorbent solution;
[0023] S5. The micron-sized organic gas adsorption material solution obtained in step S4 is subjected to a nano-sized zirconium oxide sand mill at a speed of 100-3800 r / min for 1-6 h, and after grinding, the solution is filtered and separated through an ultrafiltration membrane to obtain a nano-sized organic gas adsorption material solution;
[0024] S6. The nanoscale organic gas adsorption material solution obtained in step S5 is dried in a nanoscale spray dryer at a pressure of 10-70MPa and a temperature of 80°C-120°C to obtain a nanoscale organic gas adsorption material;
[0025] S7. The nanocomposite antibacterial agent obtained in step S3 and the nanoscale organic gas adsorption material obtained in step S6 are stirred and dispersed in a high-speed stirrer at a stirring speed of 500-2500 r / min for 5-60 min to obtain a mixed material A;
[0026] S8. Ultrapure water, aqueous resin, viscosity modifier and dispersant were sequentially added to the reactor for thorough mixing and dispersion, with a stirring speed of 300-1200 r / min for 10-20 min, and then stirred and microfiltered through a microporous membrane to remove large particles to obtain a mixed material B solution;
[0027] S9. The lubricant, surfactant and defoamer are added to a vertical vortex liquid-liquid mixer, and the mixture is stirred and mixed for 10-30 min at a speed of 100-1500 r / min, a vortex intensity of 0.5-2.5 m / s and a temperature of 5-30 ° C to obtain a mixed solution C;
[0028] S10. The mixed material A obtained in step 7 and the mixed material B solution obtained in step S8 are added to a horizontal zirconia vortex solid-liquid mixer, and stirred and mixed for 1-6 hours at a speed of 50-1800 r / min, a vortex intensity of 0.3-2.8 m / s, and a temperature of 5-30°C to obtain a mixed solution D;
[0029] S11. Add the mixed solution D of step S10 into a nano-sized zirconium oxide sand mill, grind and disperse at a speed of 500-3300 r / min for 0.5-6 h, and add the mixed solution C obtained in step S9 into five equal portions for 5 times during the grinding process. After grinding, separate the mixture by filtering with a nanofiltration membrane, and the obtained filtrate is the water-based masterbatch with fresh-keeping function suitable for corrugated paperboard.
[0030] An application of a water-based masterbatch with a fresh-keeping function applicable to a corrugated paper box, wherein the water-based masterbatch with a fresh-keeping function is used to prepare a finished corrugated paper box with a fresh-keeping effect, specifically comprising the following steps:
[0031] S12. Unbleached waste paper and logs are used as raw materials, which are pulped and mixed, and then steamed at 135-180° C. for 1-3 hours and stirred to obtain mixed pulp;
[0032] S13. The mixed pulp obtained in step S12 is subjected to a coarse screening process, a fine screening process, and a slag removal process, and then a superfine mill is used for grinding, and a retention and filtration aid and a defoaming agent are added; a water-based masterbatch with a fresh-keeping function suitable for corrugated paper boxes is added, and the mass ratio of the mixed pulp to the water-based masterbatch with a fresh-keeping function suitable for corrugated paper boxes is 80-100:5-20, and a sizing agent is added after mixing and stirring to obtain a mixed pulp with a water-based masterbatch with a fresh-keeping function;
[0033] S14. The mixed pulp obtained in step S13 is sequentially subjected to a screen forming process, a pressing process, a drying process, a calendering process and a curling process to obtain a corrugated paper having a fresh-keeping effect;
[0034] S15. The corrugated inner paper with a fresh-keeping effect obtained in step S14 is bonded to the corrugated inner paper and the corrugated outer paper, and dried to obtain a corrugated board with a fresh-keeping effect;
[0035] S16. Cut, crimp, shape and bond the corrugated paperboard obtained in step S15 to obtain a finished corrugated paper box with an inner layer having a fresh-keeping effect.
[0036] The beneficial effects of the present invention are:
[0037] 1. The water-based masterbatch with fresh-keeping function suitable for corrugated paper boxes of the present invention does not add any process in the process of making corrugated paper boxes, and does not need to be coated or sprayed after the corrugated paper or paper box is made. It only needs to add the water-based masterbatch with fresh-keeping function during mixing to make the corrugated paper with fresh-keeping effect, and then make the corrugated paper box with fresh-keeping effect in the inner layer through normal process. The operation is simple and convenient, and no adjustment or addition of any process is required, and the cost is low.
[0038] 2. The present invention is a water-based masterbatch with a fresh-keeping function suitable for corrugated paper boxes. It takes antibacterial and mildew-proofing and organic gas adsorption as the main directions, and makes its preparation process simple and efficient while meeting the national standard for food contact materials.
[0039] 3. A large amount of inorganic antibacterial ions are present in the water-based masterbatch with fresh-keeping function suitable for corrugated paper boxes of the present invention. When added to the lining paper of the corrugated paper boxes, they are closely combined with the fiber structure of the lining paper. When the metal ions in the lining paper react with bacteria through contact, the inherent components of the microorganisms are destroyed or functional disorders occur. When the microorganisms lose their activity, the metal ions will be freed from the bacteria and repeat the sterilization activity, so the antibacterial effect is long-lasting.
[0040] 4. The present invention provides a water-based masterbatch with a fresh-keeping function suitable for corrugated paperboards, wherein a variety of organic gas adsorbing materials exist, which synergize with each other and can adsorb organic gases such as ethylene produced by the respiration of fruits and vegetables to a certain extent, while the photocatalytic reaction of inorganic metal ions can also decompose ethylene to a certain extent.
[0041] 5. The nano-scale organic gas adsorption material in the water-based masterbatch with fresh-keeping function suitable for corrugated paperboards of the present invention is ground so that the nano-composite antibacterial agent loaded therein plays a sustained-release role, further enhancing the antibacterial effect and extending the fresh-keeping time. DETAILED DESCRIPTION
[0042] The preferred embodiments of the present invention are further described below:
[0043] A water-based masterbatch with a fresh-keeping function suitable for corrugated paper boxes, wherein the fresh-keeping function water-based masterbatch comprises the following components in parts by mass:
[0044]
[0045]
[0046] According to the safety standards and compliance requirements of food contact materials and products in GB4806 National Food Safety Standard, the use of additives in food contact materials and products should comply with GB9685-2016 "Standards for the Use of Additives in Food Contact Materials and Products" and relevant announcements. The above-mentioned water-based resins, nano-composite antimicrobial agents, organic gas adsorption materials, viscosity modifiers, dispersants, lubricants, surfactants, and defoamers all comply with the additives and usage requirements allowed in Table A.6 of GB9685-2016 for food contact paper and paperboard materials and products, and the scope of use and usage amount are in compliance with this standard.
[0047] The water-based resin is at least one or more of polyacrylate emulsion, polyurethane emulsion, and acrylic acid-acrylate copolymer emulsion.
[0048] The nano composite antibacterial agent is at least one or more of nano titanium dioxide, magnesium silicate, sorbic acid, borax, methyl parahydroxybenzoate, propyl parahydroxybenzoate, sodium boric oxide and sodium thiosulfate.
[0049] The organic gas adsorption material is at least one or more of silicon dioxide, silica gel, molecular sieve, diatomaceous earth and kaolin.
[0050] The viscosity modifier is at least one or more of bentonite, ethyl cellulose and hydroxyethyl cellulose.
[0051] The lubricant is at least one or more of alkyl-modified silicone oil, butyl octadecanoate, and polydimethylsiloxane.
[0052] The dispersant is at least one or more of an aluminate dispersant, a polyethylene glycol dispersant, and polyethylene oxide;
[0053] The surfactant is at least one or more of sodium succinate sulfonate, sorbitan tristearate, and polyoxyethylene sorbitan monooleate;
[0054] The defoaming agent is at least one or more of an organosilicon defoaming agent and an organic-acetylene defoaming agent.
[0055] The average particle size of the fresh-keeping functional water-based masterbatch is 0.1-500nm.
[0056] A method for preparing a water-based masterbatch with a fresh-keeping function suitable for corrugated paper boxes, the method comprising the following steps:
[0057] S1. The nano-composite antibacterial agent and ultrapure water were added to a food-grade coating-type horizontal zirconia three-roll mill, the roller pitch was adjusted to 3-5 microns, and the speed was 500-1500r / min for grinding for 0.5-5h. After grinding, the microfiltration was performed through a microporous membrane, and the filtrate was a micron-grade nano-composite antibacterial agent solution;
[0058] S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is ground by a nano-sized zirconium oxide sand mill at a speed of 100-3800 r / min for 1-6 h, and the grinding is stopped after the particle size reaches the standard of 0.1-500 nm by particle size detection, and the filtrate is filtered and separated by an ultrafiltration membrane to obtain a nanocomposite antibacterial agent solution;
[0059] S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent;
[0060] S4. The organic gas adsorbent material and ultrapure water were added to a food-grade coating-type horizontal zirconia three-roll mill, the roller pitch was adjusted to 3-5 microns, and the speed was 500-1500r / min for grinding for 0.5-5h. After grinding, the microporous membrane was microfiltered to obtain a micron-sized organic gas adsorbent solution;
[0061] S5. The micron-sized organic gas adsorption material solution obtained in step S4 is subjected to a nano-sized zirconium oxide sand mill at a speed of 100-3800 r / min for 1-6 h, and after grinding, the solution is filtered and separated through an ultrafiltration membrane to obtain a nano-sized organic gas adsorption material solution;
[0062] S6. The nanoscale organic gas adsorption material solution obtained in step S5 is dried in a nanoscale spray dryer at a pressure of 10-70MPa and a temperature of 80°C-120°C to obtain a nanoscale organic gas adsorption material;
[0063] S7. The nanocomposite antibacterial agent obtained in step S3 and the nanoscale organic gas adsorption material obtained in step S6 are stirred and dispersed in a high-speed stirrer at a stirring speed of 500-2500 r / min for 5-60 min to obtain a mixed material A;
[0064] S8. Ultrapure water, aqueous resin, viscosity modifier and dispersant were sequentially added to the reactor for thorough mixing and dispersion, with a stirring speed of 300-1200 r / min for 10-20 min, and then stirred and microfiltered through a microporous membrane to remove large particles to obtain a mixed material B solution;
[0065] S9. The lubricant, surfactant and defoamer are added to a vertical vortex liquid-liquid mixer, and the mixture is stirred and mixed for 10-30 min at a speed of 100-1500 r / min, a vortex intensity of 0.5-2.5 m / s and a temperature of 5-30 ° C to obtain a mixed solution C;
[0066] S10. The mixed material A obtained in step 7 and the mixed material B solution obtained in step S8 are added to a horizontal zirconia vortex solid-liquid mixer, and stirred and mixed for 1-6 hours at a speed of 50-1800 r / min, a vortex intensity of 0.3-2.8 m / s, and a temperature of 5-30°C to obtain a mixed solution D;
[0067] S11. Add the mixed solution D of step S10 into a nano-sized zirconium oxide sand mill, grind and disperse at a speed of 500-3300 r / min for 0.5-6 h, and add the mixed solution C obtained in step S9 into five equal portions for 5 times during the grinding process. After grinding, separate the mixture by filtering with a nanofiltration membrane, and the obtained filtrate is the water-based masterbatch with fresh-keeping function suitable for corrugated paperboard.
[0068] An application of a water-based masterbatch with a fresh-keeping function applicable to a corrugated paper box, wherein the water-based masterbatch with a fresh-keeping function is used to prepare a finished corrugated paper box with a fresh-keeping effect, specifically comprising the following steps:
[0069] S12. Unbleached waste paper and logs are used as raw materials, which are pulped and mixed, and then steamed at 135-180° C. for 1-3 hours and stirred to obtain mixed pulp;
[0070] S13. The mixed pulp obtained in step S12 is subjected to a coarse screening process, a fine screening process, and a slag removal process, and then a superfine mill is used for grinding, and a retention and filtration aid and a defoaming agent are added; a water-based masterbatch with a fresh-keeping function suitable for corrugated paper boxes is added, and the mass ratio of the mixed pulp to the water-based masterbatch with a fresh-keeping function suitable for corrugated paper boxes is 80-100:5-20, and a sizing agent is added after mixing and stirring to obtain a mixed pulp with a water-based masterbatch with a fresh-keeping function;
[0071] S14. The mixed pulp obtained in step S13 is sequentially subjected to a screen forming process, a pressing process, a drying process, a calendering process and a curling process to obtain a corrugated paper having a fresh-keeping effect;
[0072] S15. The corrugated inner paper with a fresh-keeping effect obtained in step S14 is bonded to the corrugated inner paper and the corrugated outer paper, and dried to obtain a corrugated board with a fresh-keeping effect;
[0073] S16. Cut, crimp, shape and bond the corrugated paperboard obtained in step S15 to obtain a finished corrugated paper box with an inner layer having a fresh-keeping effect.
[0074] The present application is further described below in conjunction with specific embodiments:
[0075] Example 1
[0076] S1. Add 6 parts of nano-titanium dioxide, 3 parts of sorbic acid, 6 parts of methyl paraben, 5 parts of sodium boric oxide, and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll grinder, adjust the roller pitch to 3-5 microns, grind at a speed of 500-1500r / min for 0.5-5h, and after grinding, microfiltration is performed through a microporous filter membrane to obtain a filtrate of a micron-grade nano-composite antibacterial agent solution;
[0077] S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is ground by a nano-sized zirconium oxide sand mill at a speed of 100-3800 r / min for 1-6 h, and the grinding is stopped after the particle size reaches the standard of 0.1-500 nm by particle size detection, and the filtrate is filtered and separated by an ultrafiltration membrane to obtain a nanocomposite antibacterial agent solution;
[0078] S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent;
[0079] S4. Add 5 parts of silica, 8 parts of diatomaceous earth, 7 parts of kaolin and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll mill, adjust the roller pitch to 3-5 microns, grind at a speed of 500-1500r / min for 0.5-5h, and after grinding, microfiltration is performed through a microporous filter membrane to obtain a filtrate obtained as a micron-sized organic gas adsorption material solution;
[0080] S5. The micron-sized organic gas adsorption material solution obtained in step S4 is subjected to a nano-sized zirconium oxide sand mill at a speed of 100-3800 r / min for 1-6 h, and after grinding, the solution is filtered and separated through an ultrafiltration membrane to obtain a nano-sized organic gas adsorption material solution;
[0081] S6. The nanoscale organic gas adsorption material solution obtained in step S5 is dried in a nanoscale spray dryer at a pressure of 10-70MPa and a temperature of 80°C-120°C to obtain a nanoscale organic gas adsorption material;
[0082] S7. 20 parts of the nanocomposite antibacterial agent obtained in step S3 and 20 parts of the nanoscale organic gas adsorption material obtained in step S6 are stirred and dispersed in a high-speed stirrer at a stirring speed of 500-2500r / min for 5-60min to obtain a mixed material A;
[0083] S8. 30 parts of ultrapure water, 10 parts of polyacrylate emulsion, 15 parts of polyurethane emulsion, 0.3 parts of ethyl cellulose, 0.7 parts of bentonite, 0.3 parts of aluminate dispersant and 0.5 parts of polyethylene oxide were added to the reactor for thorough mixing and dispersion, with a stirring speed of 300-1200 r / min for 10-20 min, and then stirred and microfiltered through a microporous membrane to remove large particles to obtain a mixed material B solution;
[0084] S9. 0.1 part of alkyl-modified silicone oil, 0.3 part of butyl octadecanoate, 0.6 part of polydimethylsiloxane, 0.4 part of sodium succinate sulfonate, 0.4 part of sorbitan tristearate, 0.2 part of polyoxyethylene sorbitan monooleate, and 0.5 part of an organosilicon defoamer are added to a vertical vortex liquid-liquid mixer, and the mixture is stirred and mixed for 10-30 minutes at a speed of 100-1500 r / min, a vortex intensity of 0.5-2.5 m / s, and a temperature of 5-30° C. to obtain a mixed solution C;
[0085] S10. Add the mixed material A obtained in step S7 and the mixed material B solution obtained in step S8 to a horizontal zirconia vortex solid-liquid mixer, and stir and mix at a speed of 50-1800 r / min, a vortex intensity of 0.3-2.8 m / s, and a temperature of 5-30°C for 1-6 h to obtain a mixed solution D;
[0086] S11. Add the mixed solution D of step S10 into a nano-sized zirconium oxide sand mill, grind and disperse at a speed of 500-3300 r / min for 0.5-6 h, and add the mixed solution C obtained in step S9 into five equal portions for 5 times during the grinding process. After grinding, filter and separate through a nanofiltration membrane, and bucket the filtrate to obtain a water-based masterbatch with a fresh-keeping function suitable for corrugated paperboard.
[0087] S12. Unbleached waste paper and logs are used as raw materials, which are pulped separately and then mixed. The mixed pulp is steamed at 135-180° C. for 1-3 hours and then stirred to obtain mixed pulp.
[0088] S13. The mixed pulp obtained in step S12 is subjected to a coarse screening process, a fine screening process, and a slag removal process, and then an ultrafine mill is used for grinding, and a retention and filtration aid and a defoaming agent are added; the fresh-keeping function water-based masterbatch obtained in step S11 is added, and the mass ratio of the mixed pulp to the fresh-keeping function water-based masterbatch is 80-100:5-20. After mixing and stirring evenly, a sizing agent is added to obtain a mixed pulp with a fresh-keeping function water-based masterbatch.
[0089] S14. The mixed pulp obtained in step S13 is sequentially subjected to a screen forming process, a pressing process, a drying process, a calendering process and a curling process to obtain a corrugated paper with a preservation effect.
[0090] S15. The corrugated inner paper with fresh-keeping effect obtained in step S14 is bonded to the corrugated core paper and the corrugated surface paper, and then dried to obtain a corrugated board with fresh-keeping effect.
[0091] S16. Cut, crimp, shape and bond the corrugated paperboard obtained in step S15 to obtain a finished corrugated paper box with an inner layer having a fresh-keeping effect.
[0092] Example 2
[0093] S1. Add 5 parts of magnesium silicate, 2 parts of borax, 8 parts of propyl paraben, 5 parts of sodium thiosulfate and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll mill, adjust the roller pitch to 3-5 microns, grind at a speed of 500-1500r / min for 0.5-5h, and after grinding, microfiltration is performed through a microporous filter membrane to obtain a filtrate of a micron-grade nanocomposite antibacterial agent solution;
[0094] S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is ground by a nano-sized zirconium oxide sand mill at a speed of 100-3800 r / min for 1-6 h, and the grinding is stopped after the particle size reaches the standard of 0.1-500 nm by particle size detection, and the filtrate is filtered and separated by an ultrafiltration membrane to obtain a nanocomposite antibacterial agent solution;
[0095] S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent;
[0096] S4. 7 parts of silica gel, 6 parts of molecular sieve, 7 parts of kaolin and 40 parts of ultrapure water were added to a food-grade coating type horizontal zirconia three-roll mill, the roller pitch was adjusted to 3-5 microns, and the speed was 500-1500r / min for 0.5-5h. After grinding, the microfiltration was performed through a microporous membrane, and the filtrate was taken as a micron-sized organic gas adsorption material solution;
[0097] S5. The micron-sized organic gas adsorption material solution obtained in step S4 is subjected to a nano-sized zirconium oxide sand mill at a speed of 100-3800 r / min for 1-6 h, and after grinding, the solution is filtered and separated through an ultrafiltration membrane to obtain a nano-sized organic gas adsorption material solution;
[0098] S6. The nanoscale organic gas adsorption material solution obtained in step S5 is dried in a nanoscale spray dryer at a pressure of 10-70MPa and a temperature of 80°C-120°C to obtain a nanoscale organic gas adsorption material;
[0099] S7. 20 parts of the nanocomposite antibacterial agent obtained in step S3 and 20 parts of the nanoscale organic gas adsorption material obtained in step S6 are stirred and dispersed in a high-speed stirrer at a stirring speed of 500-2500r / min for 5-60min to obtain a mixed material A;
[0100] S8. 30 parts of ultrapure water, 10 parts of polyacrylate emulsion, 15 parts of polyurethane emulsion, 0.3 parts of ethyl cellulose, 0.7 parts of hydroxyethyl cellulose, 0.3 parts of aluminate dispersant and 0.5 parts of polyethylene oxide were added to the reactor for thorough mixing and dispersion, with a stirring speed of 300-1200 r / min for 10-20 min, and then stirred and microfiltered through a microporous membrane to remove large particles to obtain a mixed material B solution;
[0101] S9. 0.1 part of alkyl-modified silicone oil, 0.3 part of butyl octadecanoate, 0.6 part of polydimethylsiloxane, 0.4 part of sodium succinate sulfonate, 0.4 part of sorbitan tristearate, 0.2 part of polyoxyethylene sorbitan monooleate, and 0.5 part of organic-acetylene defoamer are added to a vertical vortex liquid-liquid mixer, and the mixture is stirred and mixed for 10-30 minutes at a speed of 100-1500 r / min, a vortex intensity of 0.5-2.5 m / s, and a temperature of 5-30° C. to obtain a mixed solution C;
[0102] S10. Add the mixed material A obtained in step S7 and the mixed material B solution obtained in step S8 to a horizontal zirconia vortex solid-liquid mixer, and stir and mix at a speed of 50-1800 r / min, a vortex intensity of 0.3-2.8 m / s, and a temperature of 5-30°C for 1-6 h to obtain a mixed solution D;
[0103] S11. Add the mixed solution D of step S10 into a nano-sized zirconium oxide sand mill, grind and disperse at a speed of 500-3300 r / min for 0.5-6 h, and add the mixed solution C obtained in step S9 into five equal portions for 5 times during the grinding process. After grinding, filter and separate through a nanofiltration membrane, and bucket the filtrate to obtain a water-based masterbatch with a fresh-keeping function suitable for corrugated paperboard.
[0104] S12. Unbleached waste paper and logs are used as raw materials, which are pulped separately and then mixed. The mixed pulp is steamed at 135-180° C. for 1-3 hours and then stirred to obtain mixed pulp.
[0105] S13. The mixed pulp obtained in step S12 is subjected to a coarse screening process, a fine screening process, and a slag removal process, and then an ultrafine mill is used for grinding, and a retention and filtration aid and a defoaming agent are added; the fresh-keeping function water-based masterbatch obtained in step S11 is added, and the mass ratio of the mixed pulp to the fresh-keeping function water-based masterbatch is 80-100:5-20. After mixing and stirring evenly, a sizing agent is added to obtain a mixed pulp with a fresh-keeping function water-based masterbatch.
[0106] S14. The mixed pulp obtained in step S13 is sequentially subjected to a screen forming process, a pressing process, a drying process, a calendering process and a curling process to obtain a corrugated paper with a preservation effect.
[0107] S15. The corrugated inner paper with fresh-keeping effect obtained in step S14 is bonded to the corrugated core paper and the corrugated surface paper, and then dried to obtain a corrugated board with fresh-keeping effect.
[0108] S16. Cut, crimp, shape and bond the corrugated paperboard obtained in step S15 to obtain a finished corrugated paper box with an inner layer having a fresh-keeping effect.
[0109] Comparative Example 1
[0110] S1. Add 6 parts of nano-titanium dioxide, 3 parts of sorbic acid, 6 parts of methyl paraben, 5 parts of sodium boric oxide and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll mill, adjust the roller spacing to 3-5 microns, grind at a speed of 500-1500r / min for 0.5-5h, stop grinding after the particle size reaches the standard of 0.1-500nm, and microfilter through a microporous filter membrane to obtain a filtrate of a micron-grade nano-composite antibacterial agent solution;
[0111] S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is ground by a nano-sized zirconium oxide sand mill at a speed of 100-3800 r / min for 1-6 h, and then filtered and separated by an ultrafiltration membrane. The filtrate obtained is a nanocomposite antibacterial agent solution;
[0112] S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent;
[0113] S4. The nanocomposite antibacterial agent obtained in step S3, 5 parts of silicon dioxide, 8 parts of diatomaceous earth and 7 parts of kaolin were stirred and dispersed in a high-speed mixer at a stirring speed of 500-2500 r / min for 5-60 min to obtain a mixed material A;
[0114] S5. 30 parts of ultrapure water, 10 parts of polyacrylate emulsion, 15 parts of polyurethane emulsion, 0.3 parts of ethyl cellulose, 0.7 parts of bentonite, 0.3 parts of aluminate dispersant and 0.5 parts of polyethylene oxide were added to the reactor for thorough mixing and dispersion, with a stirring speed of 300-1200 r / min for 10-20 min, and then stirred and microfiltered through a microporous membrane to remove large particles to obtain a mixed material B solution;
[0115] S6. 0.1 part of alkyl-modified silicone oil, 0.3 part of butyl octadecanoate, 0.6 part of polydimethylsiloxane, 0.4 part of sodium succinate sulfonate, 0.4 part of sorbitan tristearate, 0.2 part of polyoxyethylene sorbitan monooleate, and 0.5 part of an organosilicon defoamer are added to a vertical vortex liquid-liquid mixer, and the mixture is stirred and mixed for 10-30 minutes at a speed of 100-1500 r / min, a vortex intensity of 0.5-2.5 m / s, and a temperature of 5-30° C. to obtain a mixed solution C;
[0116] S7. Add the mixed material A obtained in step S4 and the mixed material B solution obtained in step S5 to a horizontal zirconia vortex solid-liquid mixer, and stir and mix at a speed of 50-1800 r / min, a vortex intensity of 0.3-2.8 m / s, and a temperature of 5-30°C for 1-6 h to obtain a mixed solution D;
[0117] S8. Add the mixed solution D of step S7 into a nano-sized zirconium oxide sand mill, grind and disperse at a speed of 500-3300 r / min for 0.5-6 h, during which the mixed solution C obtained in step S6 is added five times in five equal portions, and after grinding, the mixed solution is separated by filtering with a nanofiltration membrane, and the filtrate is barreled to obtain a water-based masterbatch.
[0118] S9. Use unbleached waste paper and logs as raw materials, pulp them separately and then mix them, cook them at 135-180° C. for 1-3 hours, and then stir and mix them to obtain mixed pulp.
[0119] S10. The mixed pulp obtained in step S9 is subjected to a coarse screening process, a fine screening process, and a slag removal process, and then a superfine mill is used for grinding, and a retention and filtration aid and a defoaming agent are added; the water-based masterbatch obtained in step S8 is added, and the mass ratio of the mixed pulp to the water-based masterbatch is 80-100:5-20. After mixing and stirring evenly, a sizing agent is added to obtain a mixed pulp with a water-based masterbatch.
[0120] S11. The mixed pulp obtained in step S10 is sequentially subjected to a screen forming process, a pressing process, a drying process, a calendering process and a curling process to obtain corrugated paper.
[0121] S12. The corrugated inner paper obtained in step S11 is bonded to the corrugated core paper and the corrugated surface paper, and then dried to obtain a corrugated board.
[0122] S13. Cut, crimp, shape and bond the corrugated paperboard obtained in step S12 to obtain a finished inner layer corrugated paper box.
[0123] Comparative Example 2
[0124] S1. Add 7 parts of silica gel, 6 parts of molecular sieve, 7 parts of kaolin and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll mill, adjust the roller pitch to 3-5 microns, grind at a speed of 500-1500r / min for 0.5-5h, and after grinding, microfiltration is performed through a microporous filter membrane to obtain a filtrate obtained as a micron-sized organic gas adsorption material solution;
[0125] S2. The micron-scale organic gas adsorption material solution obtained in step S1 is subjected to a nano-scale zirconium oxide sand mill at a speed of 100-3800 r / min for 1-6 hours, and the grinding is stopped after the particle size reaches the standard of 0.1-500 nm after detection, and the solution is filtered and separated through an ultrafiltration membrane, and the filtrate obtained is a nano-scale organic gas adsorption material solution;
[0126] S3. The nanoscale organic gas adsorption material solution obtained in step S2 is dried in a nanoscale spray dryer at a pressure of 10-70MPa and a temperature of 80°C-120°C to obtain a nanoscale organic gas adsorption material;
[0127] S4. 5 parts of magnesium silicate, 2 parts of borax, 8 parts of propyl p-hydroxybenzoate, 5 parts of sodium thiosulfate, and the nano-scale organic gas adsorption material obtained in step S3 were stirred and dispersed in a high-speed stirrer at a stirring speed of 500-2500r / min for 5-60min to obtain a mixed material A;
[0128] S5. 30 parts of ultrapure water, 0.3 parts of ethyl cellulose, 0.7 parts of hydroxyethyl cellulose, 0.3 parts of aluminate dispersant and 0.5 parts of polyethylene oxide were added to the reactor for thorough mixing and dispersion, with a stirring speed of 300-1200 r / min for 10-20 min. After stirring, the mixture was microfiltered through a microporous filter membrane to remove large particles to obtain a mixed material B solution;
[0129] S6. 0.1 part of alkyl-modified silicone oil, 0.3 part of butyl octadecanoate, 0.6 part of polydimethylsiloxane, 0.4 part of sodium succinate sulfonate, 0.4 part of sorbitan tristearate, 0.2 part of polyoxyethylene sorbitan monooleate, and 0.5 part of an organic-acetylene defoamer are added to a vertical vortex liquid-liquid mixer, and the mixture is stirred and mixed for 10-30 minutes at a speed of 100-1500 r / min, a vortex intensity of 0.5-2.5 m / s, and a temperature of 5-30° C. to obtain a mixed solution C;
[0130] S7. Add the mixed material A obtained in step S4 and the mixed material B solution obtained in step S5 to a horizontal zirconia vortex solid-liquid mixer, and stir and mix at a speed of 50-1800 r / min, a vortex intensity of 0.3-2.8 m / s, and a temperature of 5-30°C for 1-6 h to obtain a mixed solution D;
[0131] S8. Add the mixed solution D of step S7 into a nano-sized zirconium oxide sand mill, grind and disperse at a speed of 500-3300 r / min for 0.5-6 h, during which the mixed solution C obtained in step S6 is added five times in five equal portions, and after grinding, the mixed solution is separated by filtering with a nanofiltration membrane, and the filtrate is barreled to obtain a water-based masterbatch.
[0132] S9. Use unbleached waste paper and logs as raw materials, pulp them separately and then mix them, cook them at 135-180° C. for 1-3 hours, and then stir and mix them to obtain mixed pulp.
[0133] S10. The mixed pulp obtained in step S9 is subjected to a coarse screening process, a fine screening process, and a slag removal process, and then a superfine mill is used for grinding, and a retention and filtration aid and a defoaming agent are added; the water-based masterbatch obtained in step S8 is added, and the mass ratio of the mixed pulp to the water-based masterbatch is 80-100:5-20. After mixing and stirring evenly, a sizing agent is added to obtain a mixed pulp with a water-based masterbatch.
[0134] S11. The mixed pulp obtained in step S10 is sequentially subjected to a screen forming process, a pressing process, a drying process, a calendering process and a curling process to obtain corrugated paper.
[0135] S12. The corrugated inner paper obtained in step S11 is bonded to the corrugated core paper and the corrugated surface paper, and then dried to obtain a corrugated board.
[0136] S13. The corrugated paperboard 3 obtained in step S12 is cut, embossed, formed and bonded to obtain a finished corrugated paperboard box.
[0137] Comparative Example 3
[0138] S1. Add 6 parts of nano-titanium dioxide, 3 parts of sorbic acid, 6 parts of methyl paraben, 5 parts of sodium boric oxide, and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll grinder, adjust the roller pitch to 3-5 microns, grind at a speed of 500-1500r / min for 0.5-5h, and after grinding, microfiltration is performed through a microporous filter membrane to obtain a filtrate of a micron-grade nano-composite antibacterial agent solution;
[0139] S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is ground by a nano-sized zirconium oxide sand mill at a speed of 100-3800 r / min for 1-6 h, and the grinding is stopped after the particle size reaches the standard of 0.1-500 nm by particle size detection, and the filtrate is filtered and separated by an ultrafiltration membrane to obtain a nanocomposite antibacterial agent solution;
[0140] S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent;
[0141] S4. 30 parts of ultrapure water, 10 parts of polyacrylate emulsion, 15 parts of polyurethane emulsion, 0.3 parts of ethyl cellulose, 0.7 parts of bentonite, 0.3 parts of aluminate dispersant and 0.5 parts of polyethylene oxide were added to the reactor for thorough mixing and dispersion, with a stirring speed of 300-1200 r / min for 10-20 min, and then stirred and microfiltered through a microporous membrane to remove large particles to obtain a mixed material A solution;
[0142] S5. 0.1 part of alkyl-modified silicone oil, 0.3 part of butyl octadecanoate, 0.6 part of polydimethylsiloxane, 0.4 part of sodium succinate sulfonate, 0.4 part of sorbitan tristearate, 0.2 part of polyoxyethylene sorbitan monooleate, and 0.5 part of silicone defoamer were added to a vertical vortex liquid-liquid mixer, and the mixture was stirred and mixed for 10-30 min at a speed of 100-1500 r / min, a vortex intensity of 0.5-2.5 m / s, and a temperature of 5-30° C. to obtain a mixed solution B;
[0143] S6. Add 20 parts of nano antibacterial agent, 5 parts of silicon dioxide, 8 parts of diatomaceous earth, 7 parts of kaolin and mixed material A solution into a vertical mixer, disperse at a speed of 30-200r / min for 20-180min, add mixed solution B 5 times in five equal parts during this period, and after dispersion, bucket to obtain water-based masterbatch.
[0144] S7. Use unbleached waste paper and logs as raw materials, beat them separately and then mix them, cook them at 135-180° C. for 1-3 hours, and then stir and mix them to obtain mixed pulp.
[0145] S8. The mixed pulp obtained in step S7 is subjected to a coarse screening process, a fine screening process, and a slag removal process, and then a superfine mill is used for grinding, and a retention and filtration aid and a defoaming agent are added; the water-based masterbatch obtained in step S8 is added, and the mass ratio of the mixed pulp to the water-based masterbatch is 80-100:5-20. After mixing and stirring evenly, a sizing agent is added to obtain a mixed pulp with a water-based masterbatch.
[0146] S9. The mixed pulp obtained in step S8 is sequentially subjected to a screen forming process, a pressing process, a drying process, a calendering process and a curling process to obtain corrugated paper.
[0147] S10. The corrugated inner paper obtained in step S9 is bonded to the corrugated core paper and the corrugated surface paper, and then dried to obtain a corrugated board.
[0148] S11. Cut, crimp, shape and bond the corrugated paperboard obtained in step S10 to obtain a finished inner layer corrugated paper box.
[0149] Comparative Example 4
[0150] S1. Add 7 parts of silica gel, 6 parts of molecular sieve, 7 parts of kaolin and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll mill, adjust the roller pitch to 3-5 microns, grind at a speed of 500-1500r / min for 0.5-5h, and after grinding, microfiltration is performed through a microporous filter membrane to obtain a filtrate obtained as a micron-sized organic gas adsorption material solution;
[0151] S2. The micron-sized organic gas adsorption material solution obtained in step S1 is subjected to a nano-sized zirconium oxide sand mill at a speed of 100-3800 r / min for 1-6 h, and after grinding, the solution is filtered and separated through an ultrafiltration membrane to obtain a nano-sized organic gas adsorption material solution;
[0152] S3. The nanoscale organic gas adsorption material solution obtained in step S2 is dried in a nanoscale spray dryer at a pressure of 10-70MPa and a temperature of 80°C-120°C to obtain a nanoscale organic gas adsorption material;
[0153] S4. 30 parts of ultrapure water, 0.3 parts of ethyl cellulose, 0.7 parts of hydroxyethyl cellulose, 0.3 parts of aluminate dispersant and 0.5 parts of polyethylene oxide were added to the reactor for thorough mixing and dispersion, with a stirring speed of 300-1200 r / min for 10-20 min. After stirring, the mixture was microfiltered through a microporous filter membrane to remove large particles to obtain a mixed material A solution;
[0154] S5. 0.1 part of alkyl-modified silicone oil, 0.3 part of butyl octadecanoate, 0.6 part of polydimethylsiloxane, 0.4 part of sodium succinate sulfonate, 0.4 part of sorbitan tristearate, 0.2 part of polyoxyethylene sorbitan monooleate, and 0.5 part of silicone defoamer were added to a vertical vortex liquid-liquid mixer, and the mixture was stirred and mixed for 10-30 min at a speed of 100-1500 r / min, a vortex intensity of 0.5-2.5 m / s, and a temperature of 5-30° C. to obtain a mixed solution B;
[0155] S6. Add 20 parts of nano-scale organic gas adsorption material, 5 parts of magnesium silicate, 2 parts of borax, 8 parts of propyl paraben, 5 parts of sodium thiosulfate, and mixed material A solution into a vertical mixer, disperse at a speed of 30-200r / min for 20-180min, add mixed solution B 5 times in five equal parts during this period, and after dispersion, bucket and obtain water-based masterbatch.
[0156] S7. Use unbleached waste paper and logs as raw materials, beat them separately and then mix them, cook them at 135-180° C. for 1-3 hours, and then stir and mix them to obtain mixed pulp.
[0157] S8. The mixed pulp obtained in step S7 is subjected to a coarse screening process, a fine screening process, and a slag removal process, and then a superfine mill is used for grinding, and a retention and filtration aid and a defoaming agent are added; the water-based masterbatch obtained in step S8 is added, and the mass ratio of the mixed pulp to the water-based masterbatch is 80-100:5-20. After mixing and stirring evenly, a sizing agent is added to obtain a mixed pulp with a water-based masterbatch.
[0158] S9. The mixed pulp obtained in step S8 is sequentially subjected to a screen forming process, a pressing process, a drying process, a calendering process and a curling process to obtain corrugated paper.
[0159] S10. The corrugated inner paper obtained in step S9 is bonded to the corrugated core paper and the corrugated surface paper, and then dried to obtain a corrugated board.
[0160] S11. The corrugated paperboard 3 obtained in step S10 is cut, embossed, formed and bonded to obtain a finished corrugated paperboard box.
[0161] Comparative Example 5
[0162] S1. Add 6 parts of nano-titanium dioxide, 3 parts of sorbic acid, 6 parts of methyl paraben, 5 parts of sodium boric oxide, and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll grinder, adjust the roller pitch to 3-5 microns, grind at a speed of 500-1500r / min for 0.5-5h, and after grinding, microfiltration is performed through a microporous filter membrane to obtain a filtrate of a micron-grade nano-composite antibacterial agent solution;
[0163] S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is ground by a nano-sized zirconium oxide sand mill at a speed of 100-3800 r / min for 1-6 h, and the grinding is stopped after the particle size is detected to be 30-50 nm. After grinding, the nanocomposite antibacterial agent solution is filtered and separated by an ultrafiltration membrane, and the filtrate is a nanocomposite antibacterial agent solution;
[0164] S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent;
[0165] S4. Add 5 parts of silica, 8 parts of diatomaceous earth, 7 parts of kaolin and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll mill, adjust the roller pitch to 3-5 microns, grind at a speed of 500-1500r / min for 0.5-5h, and after grinding, microfiltration is performed through a microporous filter membrane to obtain a filtrate obtained as a micron-sized organic gas adsorption material solution;
[0166] S5. The micron-sized organic gas adsorption material solution obtained in step S4 is subjected to a nano-sized zirconium oxide sand mill at a speed of 100-3800 r / min for 1-6 h, and after grinding, the solution is filtered and separated through an ultrafiltration membrane to obtain a nano-sized organic gas adsorption material solution;
[0167] S6. The nanoscale organic gas adsorption material solution obtained in step S5 is dried in a nanoscale spray dryer at a pressure of 10-70MPa and a temperature of 80°C-120°C to obtain a nanoscale organic gas adsorption material;
[0168] S7. The nanocomposite antibacterial agent obtained in step S3 and the nanoscale organic gas adsorption material obtained in step S6 are stirred and dispersed in a high-speed stirrer at a stirring speed of 500-2500 r / min for 5-60 min to obtain a mixed material A;
[0169] S8. 30 parts of ultrapure water, 10 parts of polyacrylate emulsion, 15 parts of polyurethane emulsion, 0.3 parts of ethyl cellulose, 0.7 parts of bentonite, 0.3 parts of aluminate dispersant and 0.5 parts of polyethylene oxide were added to the reactor for thorough mixing and dispersion, with a stirring speed of 300-1200 r / min for 10-20 min, and then stirred and microfiltered through a microporous membrane to remove large particles to obtain a mixed material B solution;
[0170] S9. 0.1 part of alkyl-modified silicone oil, 0.3 part of butyl octadecanoate, 0.6 part of polydimethylsiloxane, 0.4 part of sodium succinate sulfonate, 0.4 part of sorbitan tristearate, 0.2 part of polyoxyethylene sorbitan monooleate, and 0.5 part of an organosilicon defoamer are added to a vertical vortex liquid-liquid mixer, and the mixture is stirred and mixed for 10-30 minutes at a speed of 100-1500 r / min, a vortex intensity of 0.5-2.5 m / s, and a temperature of 5-30° C. to obtain a mixed solution C;
[0171] S10. Add the mixed material A obtained in step S7 and the mixed material B solution obtained in step S8 to a horizontal zirconia vortex solid-liquid mixer, and stir and mix at a speed of 50-1800 r / min, a vortex intensity of 0.3-2.8 m / s, and a temperature of 5-30°C for 1-6 h to obtain a mixed solution D;
[0172] S11. Add the mixed solution D of step S10 into a nano-sized zirconium oxide sand mill, grind and disperse at a speed of 500-3300 r / min for 0.5-6 h, during which the mixed solution C obtained in step S9 is added five times in five equal portions, and after grinding, the mixed solution is separated by filtering with a nanofiltration membrane, and the filtrate is barreled to obtain a water-based masterbatch.
[0173] S12. Unbleached waste paper and logs are used as raw materials, which are pulped separately and then mixed. The mixed pulp is steamed at 135-180° C. for 1-3 hours and then stirred to obtain mixed pulp.
[0174] S13. The mixed pulp obtained in step S12 is subjected to a coarse screening process, a fine screening process, and a slag removal process, and then a superfine mill is used for grinding, and a retention and filtration aid and a defoaming agent are added; the water-based masterbatch obtained in step S11 is added, and the mass ratio of the mixed pulp to the water-based masterbatch is 80-100:5-20. After mixing and stirring evenly, a sizing agent is added to obtain a mixed pulp with a water-based masterbatch.
[0175] S14. The mixed pulp obtained in step S13 is sequentially subjected to a screen forming process, a pressing process, a drying process, a calendering process and a curling process to obtain corrugated paper.
[0176] S15. The corrugated inner paper obtained in step S14 is bonded to the corrugated core paper and the corrugated surface paper, and then dried to obtain a corrugated board.
[0177] S16. Cut, crimp, shape and bond the corrugated paperboard obtained in step S15 to obtain a finished inner layer corrugated paper box.
[0178] Comparative Example 6
[0179] S1. Add 6 parts of nano-titanium dioxide, 3 parts of sorbic acid, 6 parts of methyl paraben, 5 parts of sodium boric oxide, and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll grinder, adjust the roller pitch to 3-5 microns, grind at a speed of 500-1500r / min for 0.5-5h, and after grinding, microfiltration is performed through a microporous filter membrane to obtain a filtrate of a micron-grade nano-composite antibacterial agent solution;
[0180] S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is ground by a nano-sized zirconium oxide sand mill at a speed of 100-3800 r / min for 1-6 h, and the grinding is stopped after the particle size is detected to be 100-200 nm. After grinding, the nanocomposite antibacterial agent solution is filtered and separated by an ultrafiltration membrane, and the filtrate is a nanocomposite antibacterial agent solution;
[0181] S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent;
[0182] S4. Add 5 parts of silica, 8 parts of diatomaceous earth, 7 parts of kaolin and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll mill, adjust the roller pitch to 3-5 microns, grind at a speed of 500-1500r / min for 0.5-5h, and after grinding, microfiltration is performed through a microporous filter membrane to obtain a filtrate obtained as a micron-sized organic gas adsorption material solution;
[0183] S5. The micron-sized organic gas adsorption material solution obtained in step S4 is subjected to a nano-sized zirconium oxide sand mill at a speed of 100-3800 r / min for 1-6 h, and after grinding, the solution is filtered and separated through an ultrafiltration membrane to obtain a nano-sized organic gas adsorption material solution;
[0184] S6. The nanoscale organic gas adsorption material solution obtained in step S5 is dried in a nanoscale spray dryer at a pressure of 10-70MPa and a temperature of 80°C-120°C to obtain a nanoscale organic gas adsorption material;
[0185] S7. The nanocomposite antibacterial agent obtained in step S3 and the nanoscale organic gas adsorption material obtained in step S6 are stirred and dispersed in a high-speed stirrer at a stirring speed of 500-2500 r / min for 5-60 min to obtain a mixed material A;
[0186] S8. 30 parts of ultrapure water, 10 parts of polyacrylate emulsion, 15 parts of polyurethane emulsion, 0.3 parts of ethyl cellulose, 0.7 parts of bentonite, 0.3 parts of aluminate dispersant and 0.5 parts of polyethylene oxide were added to the reactor for thorough mixing and dispersion, with a stirring speed of 300-1200 r / min for 10-20 min, and then stirred and microfiltered through a microporous membrane to remove large particles to obtain a mixed material B solution;
[0187] S9. 0.1 part of alkyl-modified silicone oil, 0.3 part of butyl octadecanoate, 0.6 part of polydimethylsiloxane, 0.4 part of sodium succinate sulfonate, 0.4 part of sorbitan tristearate, 0.2 part of polyoxyethylene sorbitan monooleate, and 0.5 part of an organosilicon defoamer are added to a vertical vortex liquid-liquid mixer, and the mixture is stirred and mixed for 10-30 minutes at a speed of 100-1500 r / min, a vortex intensity of 0.5-2.5 m / s, and a temperature of 5-30° C. to obtain a mixed solution C;
[0188] S10. Add the mixed material A obtained in step S7 and the mixed material B solution obtained in step S8 to a horizontal zirconia vortex solid-liquid mixer, and stir and mix at a speed of 50-1800 r / min, a vortex intensity of 0.3-2.8 m / s, and a temperature of 5-30°C for 1-6 h to obtain a mixed solution D;
[0189] S11. Add the mixed solution D of step S10 into a nano-sized zirconium oxide sand mill, grind and disperse at a speed of 500-3300 r / min for 0.5-6 h, during which the mixed solution C obtained in step S9 is added five times in five equal portions, and after grinding, the mixed solution is separated by filtering with a nanofiltration membrane, and the filtrate is barreled to obtain a water-based masterbatch.
[0190] S12. Unbleached waste paper and logs are used as raw materials, which are pulped separately and then mixed. The mixed pulp is steamed at 135-180° C. for 1-3 hours and then stirred to obtain mixed pulp.
[0191] S13. The mixed pulp obtained in step S12 is subjected to a coarse screening process, a fine screening process, and a slag removal process, and then a superfine mill is used for grinding, and a retention and filtration aid and a defoaming agent are added; the water-based masterbatch obtained in step S11 is added, and the mass ratio of the mixed pulp to the water-based masterbatch is 80-100:5-20. After mixing and stirring evenly, a sizing agent is added to obtain a mixed pulp with a water-based masterbatch.
[0192] S14. The mixed pulp obtained in step S13 is sequentially subjected to a screen forming process, a pressing process, a drying process, a calendering process and a curling process to obtain corrugated paper.
[0193] S15. The corrugated inner paper obtained in step S14 is bonded to the corrugated core paper and the corrugated surface paper, and then dried to obtain a corrugated board.
[0194] S16. Cut, crimp, shape and bond the corrugated paperboard obtained in step S15 to obtain a finished inner layer corrugated paper box.
[0195] Comparative Example 7
[0196] Comparative Example 7 is a blank corrugated box.
[0197] The following is a further elaboration of this application based on experimental analysis:
[0198] The particle size of the nanocomposite antibacterial agent was tested using Malvern Mastersizer 3000 laser particle size analyzer LPSA. The average value was taken after 10 tests. The test results are shown in Table 1.
[0199] Table 1 Test results of particle size of water-based masterbatch with fresh-keeping function
[0200]
[0201]
[0202] According to the particle size test results, the particle size of the fresh-keeping functional water-based masterbatch is within 0.1-500nm, among which Dv(50) is 32.9nm and Dv(90) is 95.2nm, that is, the main particle size of the fresh-keeping functional water-based masterbatch is distributed within 0.1-500nm.
[0203] The finished fresh-keeping corrugated paper boxes in the above-mentioned Example 1, Example 2 and Comparative Examples 1-7 were cut according to GB / T31402-2015, and the antibacterial properties of the corrugated paper boxes in Example 1, Example 2 and Comparative Examples 1-7 were tested. The average value was taken after 10 tests for each case. The test results are shown in Table 2.
[0204] Table 2 Comparison of antibacterial effects
[0205]
[0206] According to the comparison results in Table 2, when the nano-composite antibacterial agent is added and ground and dispersed with the water-based resin, the nano-composite antibacterial agent can be effectively dispersed in the water-based masterbatch with fresh-keeping function by adjusting the applicable viscosity and adding the corresponding food-grade dispersant. The surface of the nano-composite antibacterial agent is then modified by a surfactant, and the particle size distribution range of the nano-antibacterial agent is relatively wide, reaching 0.1-500nm. The synergistic effect of multiple particle sizes enhances the antibacterial activity, and the antibacterial effect is better than that of a narrow particle size distribution range and a single particle size. The nano-composite antibacterial agent is effectively loaded in the nano-organic gas adsorption material, and the antibacterial effect of the prepared water-based masterbatch with fresh-keeping function is also significantly improved. And after the materials are ground and sanded separately, the nano-composite antibacterial agent has a better effect in the whole and a higher antibacterial rate.
[0207] The organic gas adsorption rates of the fresh-keeping corrugated paperboard products in Example 1, Example 2 and Comparative Examples 1-7 were tested with reference to GB21551.4-2010. Each case was tested 10 times and the average value was taken. The test results are shown in Table 3.
[0208] Table 3 Comparison of organic gas adsorption effects
[0209]
[0210] According to the comparison results in Table 3, when organic gas adsorption materials are added, and the organic gas adsorption materials are ground, sanded, filtered and purified to prepare the fresh-keeping functional water-based masterbatch, the organic gas adsorption effect is significantly improved compared with that without adding organic gas adsorption materials.
[0211] The corrugated paper boxes with the fresh-keeping effect coating of the present invention and blank corrugated paper boxes were subjected to a banana fresh-keeping test. No. 4 color bananas were selected and placed at room temperature for 4 days. Three groups of tests were set up for each group and the average value was taken. The color number, rot rate, weight loss rate and degree of fruit stem mold were detected. The test results are shown in Table 4.
[0212] Table 4 Comparison of banana preservation effects
[0213] Test items Fresh-keeping coated corrugated paper box Blank corrugated box Color No. 4 No. 6-7 Decay rate / % 0 26.58 Weight loss rate / % 5.28 22.64 Mold degree / % No mold Obvious mold
[0214] According to the comparison results in Table 4, the corrugated paperboard with a fresh-keeping coating can effectively absorb organic gases such as ethylene produced by the respiration of fruits and vegetables, and has a greening effect; it can effectively reduce the weight loss rate of fruits and vegetables, maintain their upright state, and maintain good appearance; it can effectively inhibit the growth of bacteria, reduce the degree of mold and decay of fruits and vegetables, maintain the good appearance of fruits and vegetables, and extend the shelf life of fruits and vegetables.
[0215] Although the technical solutions of the present invention have been described and listed in detail, it should be understood that it is obvious to those skilled in the art to make modifications to the above embodiments or adopt equivalent alternatives. These modifications or improvements made without departing from the spirit of the present invention are within the scope of protection required by the present invention.
Claims
1. A water-based masterbatch with fresh-keeping function suitable for corrugated paper boxes, characterized in that: The fresh-keeping functional water-based masterbatch comprises the following components in parts by mass:
2. The water-based masterbatch with fresh-keeping function suitable for corrugated paper boxes according to claim 1, characterized in that: The water-based resin is at least one or more of polyacrylate emulsion, polyurethane emulsion, and acrylic acid-acrylate copolymer emulsion.
3. The water-based masterbatch with fresh-keeping function suitable for corrugated paper boxes according to claim 1, characterized in that: The nano composite antibacterial agent is at least one or more of nano titanium dioxide, magnesium silicate, sorbic acid, borax, methyl parahydroxybenzoate, propyl parahydroxybenzoate, sodium boric oxide and sodium thiosulfate.
4. The water-based masterbatch with fresh-keeping function suitable for corrugated paper boxes according to claim 1, characterized in that: The organic gas adsorption material is at least one or more of silicon dioxide, silica gel, molecular sieve, diatomaceous earth and kaolin.
5. The water-based masterbatch with fresh-keeping function suitable for corrugated paper boxes according to claim 1, characterized in that: The viscosity modifier is at least one or more of bentonite, ethyl cellulose and hydroxyethyl cellulose.
6. The water-based masterbatch with fresh-keeping function suitable for corrugated paper boxes according to claim 1, characterized in that: The lubricant is at least one or more of alkyl-modified silicone oil, butyl octadecanoate, and polydimethylsiloxane.
7. The water-based masterbatch with fresh-keeping function suitable for corrugated paper boxes according to claim 1, characterized in that: The dispersant is at least one or more of an aluminate dispersant, a polyethylene glycol dispersant, and polyethylene oxide; The surfactant is at least one or more of sodium succinate sulfonate, sorbitan tristearate, and polyoxyethylene sorbitan monooleate; The defoaming agent is at least one or more of an organosilicon defoaming agent and an organic-acetylene defoaming agent.
8. The water-based masterbatch with fresh-keeping function suitable for corrugated paper boxes according to claim 1, characterized in that: The average particle size of the fresh-keeping functional water-based masterbatch is 0.1-500nm.
9. A method for preparing a water-based masterbatch with a fresh-keeping function suitable for corrugated paperboard as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following steps: S1. The nano-composite antibacterial agent and ultrapure water were added to a food-grade coating-type horizontal zirconia three-roll mill, the roller pitch was adjusted to 3-5 microns, and the speed was 500-1500r / min for grinding for 0.5-5h. After grinding, the microfiltration was performed through a microporous membrane, and the filtrate was a micron-grade nano-composite antibacterial agent solution; S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is ground by a nano-sized zirconium oxide sand mill at a speed of 100-3800 r / min for 1-6 h, and the grinding is stopped after the particle size reaches the standard of 0.1-500 nm by particle size detection, and the filtrate is filtered and separated by an ultrafiltration membrane to obtain a nanocomposite antibacterial agent solution; S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent; S4. The organic gas adsorbent material and ultrapure water were added to a food-grade coating-type horizontal zirconia three-roll mill, the roller pitch was adjusted to 3-5 microns, and the speed was 500-1500r / min for grinding for 0.5-5h. After grinding, the microporous membrane was microfiltered to obtain a micron-sized organic gas adsorbent solution; S5. The micron-sized organic gas adsorption material solution obtained in step S4 is subjected to a nano-sized zirconium oxide sand mill at a speed of 100-3800 r / min for 1-6 h, and after grinding, the solution is filtered and separated through an ultrafiltration membrane to obtain a nano-sized organic gas adsorption material solution; S6. The nanoscale organic gas adsorption material solution obtained in step S5 is dried in a nanoscale spray dryer at a pressure of 10-70MPa and a temperature of 80°C-120°C to obtain a nanoscale organic gas adsorption material; S7. The nanocomposite antibacterial agent obtained in step S3 and the nanoscale organic gas adsorption material obtained in step S6 are stirred and dispersed in a high-speed stirrer at a stirring speed of 500-2500 r / min for 5-60 min to obtain a mixed material A; S8. Ultrapure water, aqueous resin, viscosity modifier and dispersant were sequentially added to the reactor for thorough mixing and dispersion, with a stirring speed of 300-1200 r / min for 10-20 min, and then stirred and microfiltered through a microporous membrane to remove large particles to obtain a mixed material B solution; S9. The lubricant, surfactant and defoamer are added to a vertical vortex liquid-liquid mixer, and the mixture is stirred and mixed for 10-30 min at a speed of 100-1500 r / min, a vortex intensity of 0.5-2.5 m / s and a temperature of 5-30 ° C to obtain a mixed solution C; S10. The mixed material A obtained in step 7 and the mixed material B solution obtained in step S8 are added to a horizontal zirconia vortex solid-liquid mixer, and stirred and mixed for 1-6 hours at a speed of 50-1800 r / min, a vortex intensity of 0.3-2.8 m / s, and a temperature of 5-30°C to obtain a mixed solution D; S11. Add the mixed solution D of step S10 into a nano-sized zirconium oxide sand mill, grind and disperse at a speed of 500-3300 r / min for 0.5-6 h, and add the mixed solution C obtained in step S9 into five equal portions for 5 times during the grinding process. After grinding, separate the mixture by filtering with a nanofiltration membrane, and the obtained filtrate is the water-based masterbatch with fresh-keeping function suitable for corrugated paperboard.
10. An application of a water-based masterbatch with a fresh-keeping function suitable for corrugated paperboard as claimed in any one of claims 1 to 8, characterized in that: The fresh-keeping functional water-based masterbatch is used to prepare a finished corrugated paper box with a fresh-keeping effect, which specifically includes the following steps: S12. Unbleached waste paper and logs are used as raw materials, which are pulped and mixed, and then steamed at 135-180° C. for 1-3 hours and stirred to obtain mixed pulp; S13. The mixed pulp obtained in step S12 is subjected to a coarse screening process, a fine screening process, and a slag removal process, and then a superfine mill is used for grinding, and a retention and filtration aid and a defoaming agent are added; a water-based masterbatch with a fresh-keeping function suitable for corrugated paper boxes is added, and the mass ratio of the mixed pulp to the water-based masterbatch with a fresh-keeping function suitable for corrugated paper boxes is 80-100:5-20, and a sizing agent is added after mixing and stirring to obtain a mixed pulp with a water-based masterbatch with a fresh-keeping function; S14. The mixed pulp obtained in step S13 is sequentially subjected to a screen forming process, a pressing process, a drying process, a calendering process and a curling process to obtain a corrugated paper having a fresh-keeping effect; S15. The corrugated inner paper with a fresh-keeping effect obtained in step S14 is bonded to the corrugated inner paper and the corrugated outer paper, and dried to obtain a corrugated board with a fresh-keeping effect; S16. Cut, crimp, shape and bond the corrugated paperboard obtained in step S15 to obtain a finished corrugated paper box with an inner layer having a fresh-keeping effect.